1958
DOI: 10.1161/01.res.6.6.810
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Distribution of Red Cells and Albumin in the Dog Kidney

Abstract: labeled red cells mid I 131 huniiin serum iilbumin were injected intrnvenously into S mongrel dogs. After 1 hour kidneys were removed and frozen rapidly with dry ice. Sections of outer cortex, inner cortex, outer medulla, inner niedulhi, outer pnpilln nnd inner papilla were removed and analyzed for Cr 111 and I 181 radioactivity. Tissue mdioactivity was compared with that of arterial blond and concentrations of labeled red cells and albumin were calculated. No significant difference was found in relative red c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…An average cortical red cell volume of 8%o (17)(18)(19)(20) Fig. 7, which includes four measurements during control and retransfusion in addition to those given in Table III blood volume to be constant.…”
Section: Resultsmentioning
confidence: 99%
“…An average cortical red cell volume of 8%o (17)(18)(19)(20) Fig. 7, which includes four measurements during control and retransfusion in addition to those given in Table III blood volume to be constant.…”
Section: Resultsmentioning
confidence: 99%
“…A falsely high value for RBF would also result if indocyanine green-labeled albumin equilibrated in a single renal circulation with an extravascular albumin compartment. Such a "loss" of intravascular albumin does not normally occur (20), but abnormally rapid extravascular distribution of albumin in these patients cannot be ruled out. Indeed, patient 21 had a somewhat larger calculated vascular volume than the other patients in this series, suggesting the possibility of an unusually large albumin space.…”
Section: Clinical Observationsmentioning
confidence: 88%
“…In comparison, several investigators found the sum of renal distribution spaces of labelled red blood cells (R.B.C.s) and albumin to be more than twice this value. Thus Lilienfield, Rose & Lassen (1958) reported a value of 32-8 ml./100 g and from the data given by Emery, Gowenlock, Riddel & Black (1959) an average of 35-1 ml./100 g whole kidney may be calculated. For cat kidneys, Pappenheimer & Kinter (1956) reported a figure of 31-0 ml./100 g. Values reported by Ulfendahl (1962) were smaller and ranged between 14-0 and 22-3 ml./100 g tissue for cat and rabbit kidneys under various diuretic conditions.…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that a fraction of plasma albumin in the kidney is present in the interstitial space (Pappenheimer & Kinter, 1956;Lilienfield et al 1958;Swann, 1960). With histological techniques Pomerantz, Slotkoff & Lilienfield (1965) found albumin, marked with a fluorescent dye, in the renal interstitium, but this observation was not confirmed by Carone, Everett, Blondeel & Stolarczyk (1967).…”
Section: Introductionmentioning
confidence: 99%